Cultural Life in Turkestan and Bukhara at the End of the 19th Century at the Beginning of the 20th Century, the Educational Activities of Sadriddin Ayniy - Kurbanova Nigina Bobokhoyevna (International Journal on Integrated Education, 2026)
this article presents socio-cultural life in Turkestan and Bukhara in the late 19th and early 20th centuries, pedagogical views of Sadriddin Ayni on madrasa education, scientific-theoretical analysis on the content and methods of the lesson in madrasas.